Strategi Komunikasi Samsat Medan Utara Dalam Mensosialisasikan Program Mandiri Ketuk Pintu Bagi Masyarakat Penunggak Pajak Kendaraan - Faizal Hamzah Lubis; Namira Namira (Universitas Muhammadiyah Sumatera Utara, 2023)
The self-knock on door program is the latest solution from the North Medan Samsat for people who are in arrears of vehicle tax, this self-knock on door program has a very important role for the community to continue to fulfill compliance in paying PKB. The type of research used in this research is descriptive qualitative research. which aims to understand social and human phenomena by creating comprehensive and complex accounts presented using words, reporting detailed views obtained from an information source. The researcher acts as a key instrument, sampling, data sources are carried out purposively and snowball, data collection techniques are triangulation (combined) namely about communication patterns of the North Medan Samsat Office towards Motor Vehicle Taxpayers in Medan City . The results showed that tax services, tax sanctions and income levels had a significant effect on taxpayer compliance in paying motor vehicle taxes at the North Medan Samsat